Tokoh Terbilang history game using role playing game / Che Muhammad Syafiq Che Mat Noor - Che Mat Noor, Che Muhammad Syafiq (Faculty of Computer and Mathematical Sciences, 2017)
Tokoh Terbilang History Game is a stand-alone game that helped students to learn history subject for primary student Standard Four. This game is for students who need study history subject but in different ways. Tokoh Terbilang is one the subtopic in history subject that represent two important figure that students can take them as role model is real life. There are difficult to understand and attract to learn history subject based on survey and interview, there are students need to read the textbook but hard to understand because they are not get clear picture of the events that happened. Otherwise, student boring to study history subject because teachers using old learning method “talk and chalk” without give an explanation. This game is designed by using chosen Software Development Kit (SDK) because to edit the components that needed for this game. The objectives of this game is to design a game to teach student about the history of Tokoh Terbilang History Game using Role Playing Games (RPG) method. Second objective to develop the designed game using chosen Software Development Kit (SDK). Last objective is to test the usability of the game. Research Methodology used is ADDIE model. Testing has been carried out by 5 students from Sekolah Kebangsaan Sri Mendapat. The whole result shown that students satisfy with game and easy to understand with the content in the game. Overall, there are still enhancement that could be proposed for this project in the future such as add more mission in this game and building this game in mobile phone application.